Learning What I Need to Know: Experiences of Rural Cardiac Surgery Patients - Martha M Scheckel; Jennifer Hedrick-Erickson; Debra Stieve (Rural Nurse Organization; Binghamton University, 2020)
Purpose: This hermeneutic study expands understandings of rural cardiac surgery patients' experiences of their learning needs following cardiac surgery to inform the provision of patient education for this population. Sample: Eighteen rural residents provided accounts about their experiences. Findings: An interpretation as analysis approach revealed three themes: a) Learning: Family History Informing Preventive Care; b) Learning: The Notebook, Blue's Clues, and Explanations; and c) Learning: Lifestyle Changes and Confronting Mortality. Conclusions: The first theme demonstrates needs to ensure patients from rural settings understand that preventing cardiovascular disease is not limited to family members' experiences with secondary and tertiary prevention. The second theme underscores the importance of providing patient education materials that are readable and useable, and considers existential learning needs. The last theme highlights the importance of patients understanding how lifestyle changes involve embracing new ways of living that are enhanced through cardiac rehabilitation, and yet, can be experienced as life limiting. DOI: http://dx.doi.org/10.14574/ojrnhc.v20i1.605